Dynamic capabilities and innovation capabilities: The case of the ‘Innovation Clinic’ - Fred Strønen; Thomas Hoholm; Kari Kværner; Linn Nathalie Støme (Journal of Entrepreneurship, Management and Innovation)

(untitled)
In this explorative study, we investigate the relationship between dynamic capabilities and innovation capabilities. Dynamic capabilities are at the core of strategic management in terms of how firms can ensure adaptation to changing environments over time. Our paper follows two paths of argumentation. First, we review and discuss some major contributions to the theories on ordinary capabilities, dynamic capabilities, and innovation capabilities. We seek to identify different understandings of the concepts in question, in order to clarify the distinctions and relationships between dynamic capabilities and innovation capabilities. Second, we present a case study of the ’Innovation Clinic’ at a major university hospital, including four innovation projects. We use this case study to explore and discuss how dynamic capabilities can be extended, as well as to what extent innovation capabilities can be said to be dynamic. In our conclusion, we discuss the conditions for nurturing ‘dynamic innovation capabilities’ in organizations.